Transylvanian Health Database: A Historical Database of Medicalization Spreading in Transylvania Before 1918 - Dumănescu , Luminița; Hegedűs, Nicoleta; Lumezeanu , Angela (Studia Historiae Oeconomicae, 2022)
Providing valuable research on social history is, nowadays, impossible without the use of complex digital tools capable of providing, through appropriate interrogation, comprehensive answers to the researchers' increasingly varied research questions. The development of Historical Population Database (HPDT) has brought us closer to other research problems that require the input of digital tools in order to be investigated as widely as possible. One of these is the process of medicalization of Transylvania, a historical topic about which there are relatively few and rather narrow approaches. On the basis of administrative and sanitary directories, various other sources referring to the allocation of doctors' posts in the communes and the filling of these posts, medical reports, press, publications, statistics, parish registers and other sources related to the medical situation, we have built the Transylvania Health Database (THD), a research tool that is expected to be released for public use by the end of 2022. THD is a method-oriented database, built in MySQL, whose presentation can be used for the implementation of similar projects in the Eastern European area, which is still underdeveloped in terms of digital tools useful to researchers.